Prospek dan Tantangan Perkembangan Asuransi Syariah di Kota Binjai - Rifaldi Ahmad Nasution; Fauzi Arif Lubis (Universitas Katolik Widya Karya Malang, 2023)
This study discusses the prospects and challenges of sharia insurance development in Binjai City. The study used descriptive qualitative research with data collection techniques through literature studies, such as books, internet, trusted websites and previous journals. The purpose of this research is to understand how the prospects and challenges for the growth of sharia insurance in Binjai City are. Therefore, the results obtained from the study are proving that sharia insurance products continue to experience growth with positive strong encouragement from the community, where people benefit from sharia insurance. In addition, the challenges faced by sharia insurance companies such as many people who do not fully know the existence of sharia insurance. Therefore, it is very necessary for the main role of the government to make sharia insurance experience optimal development and growth